A systematic literature review on the impact of E-HRM - Ben Delos Chie; Borhan Abdullah (Science International, 2022)
It's becoming more common for businesses to use electronic Human Resource Management (e-HRM) and it's also a topic of interest to new researchers. For the last two decades, this study has done a systematic literature review to look at all of the research on the adoption and effects of e-HRM that has been done. This study is an attempt help the future research on e-HRM. It’s an new look at a few examples shows that e-HRM can make a big difference: It can be operational, relational, and even change the way people work together. There has been a shift in the debate over the years from operational gains to strategic gains. The success of e-HRM is very important for these benefits to come to fruition. Human, technological, organizational, and environmental factors all play a role in whether or not people use it. Our research looks into these factors in more detail and says that more research is needed to figure out how adoption factors and the benefits of e-HRM are linked.